Nutritional support to maintain proper immune status during intense training - Gleeson, M. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Prolonged exercise and heavy training are associated with depressed immune function which can increase the risk of picking up minor infections. To maintain robust immunity, athletes should eat a well-balanced diet sufficient to meet their energy, carbohydrate, protein, and micronutrient requirements. Dietary deficiencies of protein and specific micronutrients have long been associated with immune dysfunction and an adequate intake of iron, zinc, and vitamins A, D, E, B6 and B12 is particularly important in the maintenance of immune function. Consuming carbohydrate during prolonged strenuous exercise attenuates rises in stress hormones and appears to limit the degree of exercise-induced immune depression. Similar effects can be seen with daily ingestion of high-dose antioxidant vitamin supplements, though concerns have been expressed that excessive antioxidant intake may impair exercise training adaptations. It is safe to say with reasonable confidence that individual amino acids, colostrum, Echinacea, and zinc are unlikely to boost immunity or reduce infection risk in athletes. The ingestion of carbohydrate during exercise and daily consumption of probiotic and plant polyphenol (e.g. quercetin)-containing supplements or foodstuffs (e.g. non-alcoholic beer) currently offer the best chance of success. This approach is likely to be most effective for individuals who are particularly prone to illness.